Analysis of Innovation and Investment in the Activities of Agricultural Industry in Achieving Financial Stability (Czech Journal of Multidisciplinary Innovations, 2022)
In this article, the practice of the World Economy shows that integration processes in agricultural production cannot develop independently in ensuring innovative financial management. Given that these processes are very slow, the state should encourage these processes, including the creation of clusters, to the fullest extent possible. To do this, first of all, it is necessary to systematize the assessment indicators that ensure financial stability and determine the possible effectiveness of the creation of clusters in the territory of the Republic of Uzbekistan.